THE CONTRIBUTION OF AYURVEDIC CLASSICS ON KSHUDRA ROGA WITH SPECIAL REFERENCE TO COSMETIC DISEASES (International Journal of Ayurveda and Pharma Research, 2016)
Cosmetic dermatology might be defined as that aspects of the practice of dermatology that emphasizes looking good. while cutaneous medicine and surgery focuses on the diagnosis, treatment and prevention of skin diseases. Patients who seek relief from worry lines or acne scars are obviously cosmetic patients. Other patients who have medical skin problems may also have cosmetic concerns and all of them want to look good and are part of the practice of cosmetic dermatology. So, there is a significant aspect of the specialty directed towards improving the patients appearance. Nowadays, cosmetic diseases are challenging in modern era as there is limitations to current treatment and likely to be treated as insignificant and inconsequential in comparison to other diseases. This study aims to shed light on often neglected topic, Kshudra roga which includes many diseases which affects ones external beauty, is needed to be enlighten for making development in this field. Some of the diseases of Kshudra roga mentioned in ancient Ayurvedic classics are cosmetic diseases of present era like Khalitya (alopecia), Palitya (premature greying of hair), Yawon pidika (acne vulgaris), Darunak (seborrhic dermatitis or dandruff), Jatumani (birth mark), Kunakha (discolouration of nails) etc. This diseases are challenging and its treatment given to the patient are sometimes not satisfactory and it's not cost effective, provided by the modern medicine. But in the ancient Ayurvedic classics, the cause, symptoms and their specific treatment had been described thousands of years back. For developing this knowledge and to bring it out for the use of the people through research is a need of the hour. So emphasizing in it will serve an effective development and contribution regarding the field of cosmetic diseases.